Differences in game-based performance by playing position in young elite male team handball players - Wagner, H.; Radic, V.; Hinz, M. (Frontiers in Sports and Active Living, 2025)
Introduction: In male team handball, different playing positions have different demands due to their tactical roles. However, if the game-based physical performance differs across playing positions has not been analyzed, although this is crucial for training young elite players to reach a world-class level based on their specific positions. Consequently, the aim of this study was to analyze game-based performance in young elite male team handball players based on their playing positions.